2008
DOI: 10.1016/j.exppara.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A contractile vacuole complex is involved in osmoregulation in Trypanosoma cruzi

Abstract: Acidocalcisomes are dense, acidic organelles with a high concentration of phosphorus present as pyrophosphate and polyphosphate complexed with calcium and other cations. Acidocalcisomes have been linked to the contractile vacuole complex in Chlamydomonas reinhardtii, Dictyostelium discoideum, and Trypanosoma cruzi. A microtubule-and cyclic AMP-mediated fusion of acidocalcisomes to the contractile vacuole complex in T. cruzi results in translocation of aquaporin and the resulting water movement which, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 77 publications
2
89
0
3
Order By: Relevance
“…Fusion of acidocalcisomes with the contractile vacuole, and the concomitant hydrolysis of polyP has been postulated to lead to an increase in phosphate and cations in the bladder, resulting in water accumulation Rohloff and Docampo, 2008). These changes are likely to be accompanied by the transfer of a phosphate transporter and cation exchangers (Ulrich et al, 2011) from the acidocalcisome membranes, together with TcAQP1 , providing the means for water accumulation (through TcAQP1), as well as for the return of cations (cation exchangers) and phosphate (P i transporter) to the cytosol after water elimination .…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of acidocalcisomes with the contractile vacuole, and the concomitant hydrolysis of polyP has been postulated to lead to an increase in phosphate and cations in the bladder, resulting in water accumulation Rohloff and Docampo, 2008). These changes are likely to be accompanied by the transfer of a phosphate transporter and cation exchangers (Ulrich et al, 2011) from the acidocalcisome membranes, together with TcAQP1 , providing the means for water accumulation (through TcAQP1), as well as for the return of cations (cation exchangers) and phosphate (P i transporter) to the cytosol after water elimination .…”
Section: Discussionmentioning
confidence: 99%
“…These structures seem to be involved in process of osmoregulation. It has been shown that fusion of acidocalcisomes to the contractile vacuole takes place via a process mediated by cyclic adenosine monophosphate (Rohloff & Docampo 2008).…”
Section: The Contractile Vacuolementioning
confidence: 99%
“…In addition, our knowledge of how the CV cycle is controlled and adapted to the need of the cell is at best fragmentary. Calcium, protein kinases and cAMP have been implicated (Rohloff and Docampo, 2008), but in no system is the CV really understood.…”
Section: Introductionmentioning
confidence: 99%